IMPLEMENTASI PROGRAM MADRASAH LITERASI DALAM MENINGKATKAN BUDAYA MEMBACA DAN MENULIS SISWA DI MA DARUT TAQWA - Sayida Nurul Qomariyah; Fachrudin Yusuf, Wiwin; Mubarok, Achmat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Madrasah Literacy Program in improving students’ reading and writing culture at MA Darut Taqwa. This study employs a qualitative approach with a descriptive research design. Data were collected through observation, in-depth interviews, and documentation involving the madrasah’s vice principal for curriculum, the head of the literacy team, literacy instructors, and students actively participating in the literacy program. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, while data validity was strengthened through triangulation of sources and techniques. The results of the study indicate that the implementation of the Madrasah Literacy Program was carried out through the habit of reading before lessons, writing guidance, the provision of literacy facilities, the provision of motivation and appreciation, as well as the publication of students’ works in the form of ISBN-registered books. This program has a positive impact on the development of students’ reading and writing culture, as evidenced by increased reading interest, improved reading comprehension skills, greater confidence in expressing ideas through writing, and the emergence of students’ creative works in the form of poetry, short stories, and novels. As of the time of this study, a total of 24 ISBN-registered books have been successfully published as the result of students’ work through the madrasah literacy program. Nevertheless, the implementation of the program still faces several challenges, such as low reading interest among some students, the influence of gadget use, time constraints, and the lack of consistent support from all educators. This study indicates that the Madrasah Literacy Program at MA Darut Taqwa not only serves to cultivate reading and writing habits but also fosters a productive and sustainable literacy ecosystem within the madrasah environment.